Proliferation and Bifurcation of the Sufi Orders in Twentieth-Century Egypt - Jong, Frederick de, (Middle East and Islamic Studies E-Books Online, Collection 2024., 2025)
This study covers a period of some seventy-five years, from the abolition of right of qadam (priority) in 1905 until the adoption of the Law Concerning the Regulations for the Sufi Orders of 1976 by the Egyptian Parliament. During this period, regulations for the Sufi orders were contested and remained in limbo when amendments proposed by the shaykhs of the orders continued to be rejected by the mufti of Egypt. The abolition of right of qadam generated a proliferation of Sufi orders. A core realm of sufi orders recognized by the authorities was known as "official Sufi orders". A larger group of Sufi orders emerged which did not have official recognition and was referred to as "free Sufi orders". The history of the Sufi orders in both categories in the post- qadam era is at the centre of the present study.